Synergistic Use of Single-Pass Interferometry and Radar Altimetry to Measure Mass Loss of NEGIS Outlet Glaciers between 2011 and 2014 - Lukas Krieger; Undine Strößenreuther; Veit Helm; Dana Floricioiu; Martin Horwath (Remote Sensing, 2020)
Mass balances of individual glaciers on ice sheets have been previously reported by forming a mass budget of discharged ice and modelled ice sheet surface mass balance or a complementary method which measures volume changes over the glaciated area that are subsequently converted to glacier mass change. On ice sheets, volume changes have been measured predominantly with radar and laser altimeters but InSAR DEM differencing has also been applied on smaller ice bodies. Here, we report for the first time on the synergistic use of volumetric measurements from the CryoSat-2 radar altimetry mission together with TanDEM-X DEM differencing and calculate the mass balance of the two major outlet glaciers of the Northeast Greenland Ice Stream: Zachariæ Isstrøm and Nioghalvfjerdsfjorden (79North). The glaciers lost 3.59 ± 1.15 G t a − 1 and 1.01 ± 0.95 G t a − 1 , respectively, between January 2011 and January 2014. Additionally, there has been substantial sub-aqueous mass loss on Zachariæ Isstrøm of more than 11 G t a − 1 . We attribute the mass changes on both glaciers to dynamic downwasting. The presented methodology now permits using TanDEM-X bistatic InSAR data in the context of geodetic mass balance investigations for large ice sheet outlet glaciers. In the future, this will allow monitoring the mass changes of dynamic outlet glaciers with high spatial resolution while the superior vertical accuracy of CryoSat-2 can be used for the vast accumulation zones in the ice sheet interior.